Kedampingan Hewan Penghela pada Industri Gula di Jawa Abad XX - Hadi, Putro Wasista (Universitas Gadjah Mada, 2024)
This research discusses the relationship of draft animals and humans in Java has been historically intertwined, reaching a turning point at the end of the 19th century. This period saw the initiation of various industries, especially sugar factory, ethical awareness regarding the welfare of animals, as well as a collective awareness of the identity of a new of Indonesian society and workers. Consequently, the concept of human-animal relationship periodically undergoes changes to harmonize with the new world order. As a result, the values of human-animal relationship, and especially humans with nature, are now characterized by relationships that are always based on transactional relations. This results in the dissolution of the identity of Javanese society, which has a close relationship with nature and animals in line with the concept of “underworld and upperworld”. This article uses historical method with the approachment of environmental history. The primary sources for this article are contemporaneous newspapers, PG Gondang Baru’s 1958 Annual Report, and other documents in the form of contemporaneous photographs, complemented by other secondary references.